And justice for all : an oral history of the Japanese American detention camps - Tateishi, John, 1939- (University of Washington Press, 1999)
Personal accounts of Japanese Americans kept in relocation camps during World War II express experiences with riots, unsanitary conditions, poor medical care, government inqueries, and divided families.